1992
DOI: 10.1161/01.cir.86.5.1351
|View full text |Cite
|
Sign up to set email alerts
|

Active skeletal muscle mass and cardiopulmonary reserve. Failure to attain peak aerobic capacity during maximal bicycle exercise in patients with severe congestive heart failure.

Abstract: In contrast to normal subjects and patients with moderate CHF, patients with severe CHF do not exhaust their cardiopulmonary reserve during symptom-limited maximal LL exercise on a bicycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
5

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 39 publications
(6 reference statements)
3
48
0
5
Order By: Relevance
“…Furthermore, the intramuscular pH was more severely lowered in the CHF patients than in controls. 15 Taken together with the findings from Jondeau et al 20 and LeJemtel, skeletal muscle metabolism reaches its limit at the end of exercise, even with considerable cardiac reserve, in patients with CHF. 15, 20 Thus, skeletal muscle metabolism limits the exercise capacity of CHF patients.…”
Section: Does Skeletal Muscle Metabolism Limit Exercise Capacity In Chf?mentioning
confidence: 79%
“…Furthermore, the intramuscular pH was more severely lowered in the CHF patients than in controls. 15 Taken together with the findings from Jondeau et al 20 and LeJemtel, skeletal muscle metabolism reaches its limit at the end of exercise, even with considerable cardiac reserve, in patients with CHF. 15, 20 Thus, skeletal muscle metabolism limits the exercise capacity of CHF patients.…”
Section: Does Skeletal Muscle Metabolism Limit Exercise Capacity In Chf?mentioning
confidence: 79%
“…Second, the patients enrolled in this study had mild CHF, so the various relationships observed in this study may not be applicable to moderate to severe CHF 16 in which there is not only impaired pump function but also quantitative and qualitative changes of the skeletal muscle that may strongly affect exercise capacity. 9 Third, the correlations among variables as shown in Fig 2 should each be primarily evaluated in normal subjects and CHF patients. In this study, each relationship among the variables was evaluated together because of the small population, and considering a continuous group from sedentary volunteers to mild CHF patients.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In the present study, we compared normal subjects with patients with mild CHF because Jandeau et al 9 has previously demonstrated that the limiting factor for exercise capacity is cardiopulmonary reserve in both groups, but is peripheral muscle itself in patients with moderate to severe CHF. 9 We hypothesized that redistribution of blood flow from the non-exercising tissues to the working skeletal muscle during exercise would be blunted, in addition to impairment of the exercise-induced reduction of systemic vascular resistance (SVR), possibly leading to a reduction in the exercise capacity of patients with mild CHF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17] Além disso, o aumento no débito cardíaco agudo provocado por drogas não melhora a tolerância aos esforços físicos na insuficiência cardíaca. 18,19 Por fim, Jondeau et al (1992) 20 mostraram em um estudo bem delineado que as lesões periféricas, e não a redução no débito cardí-aco, limitam a maioria dos pacientes com insuficiên-cia cardíaca. Eles viram que a frequência cardíaca e o consumo de oxigênio aumentaram na maioria dos pacientes adicionando um exercício com os membros superiores após o consumo de oxigênio ter atingido platô em exercício em bicicleta até a exaustão.…”
Section: Introductionunclassified